Pengaruh Senam Prolanis terhadap Tekanan Darah Lansia - Hieronimous Amandus; Susito Susito; Yuliana Ninik; M. Ibraar Ayatullah (Jurnal Kesehatan Manarang, 2018)
Elderly is a part in the process of human development. Elderly is not a disease, but an advanced stage of the life process was characterized by a decrease in the body's ability to adapt to environmental stress. Increased incidence of chronic diseases in the elderly include heart disease, blood vessels, high blood pressure, diabetes mellitus, rheumatism and so on due to poor and sedentary lifestyles so that the morbidity rate in the elderly increases. Non-pharmacological treatment for the elderly one of them is by doing activities related to physical activities such as exercise in the elderly. Prolanis gymnastics is one of the government programs carried out on the elderly with the aim of reducing morbidity due to degenerative diseases experienced by the elderly such as hypertension. Prolanis gymnastics is light and easy to do and does not burden the elderly. The aim of the study was to determined the effect of prolanis gymnastics on blood pressure reduction. The method in this study is quasi experimental pre-post test with one experimental group. Samples from 12 people used purposive sampling. Data analysis was used Paired Sample t-test to find out different tests. Results: There is a significant difference between blood pressure before and after prolanis exercise with P Value = 0,000 or p < 0.05. Conclusions in this study indicate that prolanis gymnastics is effective in reducing blood pressure in elderly people with hypertension. Physical activity carried out regularly in the elderly can make a positive contribution in reducing blood pressure, so as to improve the quality of life and productivity of the elderly.